The origins of money in the Iron Age Mediterranean world - Heymans, Elon (Cambridge University Press, 2021)
Color versions of select print images available on the Resources tab (or here: www.cambridge.org/heymans). This book shows how money emerged and spread in the eastern Mediterranean, centuries before the invention of coinage. While the invention of coinage in Ancient Lydia around 630 BCE is widely regarded as one of the defining innovations of the ancient world, money itself was never invented. It gained critical weight in the Iron Age (ca. 1200 - 600 BCE) as a social and economic tool, most dominantly in the form of precious metal bullion. This book is the first study to comprehensively engage with the early history of money in the Iron Age Mediterranean, tracing its development in the Levant and the Aegean. Building on a detailed study of precious metal hoards, Elon D. Heymans deploys a wide range of sources, both textual and material, to rethink money's role and origins in the history of the eastern Mediterranean.